Brand Image as a Mediator Between Green Marketing, Price, and Consumer Purchase Decisions at Starbucks Coffee - Lailia Afifah; Muhammad Ridwan Basalamah; Ahmad Subhan Mahardani (LP2M IAIN Palopo, 2026)
This study aims to analyze the role of Brand Image in mediating the influence of Green Marketing and Price on the Purchase Decision of Starbucks Coffee consumers in Malang City. The research method used a quantitative approach with a purposive sampling technique on 105 respondents, and data analysis was carried out through Structural Equation Modeling (SEM) based on Partial Least Square (PLS) using SmartPLS. The results of the study show that Green Marketing has a positive but insignificant effect on purchase decisions, while Price has a positive and significant effect. In addition, Green Marketing and Price have been proven to have a significant effect on Brand Image, which in turn has a positive effect on purchase decisions. Another important finding is that Brand Image is able to mediate the influence of Green Marketing and Price on purchase decisions. Theoretically, this study strengthens the study of consumer behavior by placing Brand Image as a mediating variable, while practically providing implications for Starbucks to maintain the quality of products and services while strengthening sustainability programs so that brand image is more positive and consumer purchasing decisions increase.